2015
DOI: 10.1007/s11306-015-0774-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preanalytical sampling conditions on the 1H NMR metabolic profile of human blood plasma and introduction of the Standard PREanalytical Code used in biobanking

Abstract: Variations in sample collection, processing and storage within the field of clinical metabolomics might hamper its effective implementation. In this study, the impact of relevant preanalytical conditions on the plasma 1 H NMR metabolic profile was examined. The biobanking community recently developed a method for coding preanalytical conditions called the Standard PREanalytical Code (SPREC). It is envisaged that SPREC will ultimately identify which samples are fit for a particular analysis, based on prior vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…To our knowledge, several parameters, such as individual variations of centrifugation times or rotational speeds evaluated both on plasma and serum 1 H NMR metabolic profiles, are reported here for the first time, while others have previously been investigated on very small sets of samples [25,26,27,28,29,30,31,32]. Several studies have focused on defining standard pre-analytical guidelines for omics investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, several parameters, such as individual variations of centrifugation times or rotational speeds evaluated both on plasma and serum 1 H NMR metabolic profiles, are reported here for the first time, while others have previously been investigated on very small sets of samples [25,26,27,28,29,30,31,32]. Several studies have focused on defining standard pre-analytical guidelines for omics investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the UK biobank showed that storage of serum spectra at 4 °C for 24 h before freezing significantly affects the NMR-based metabolic profile [25]. Clot time, clot temperature as well as the number of freeze-thaw cycles have also been shown to influence NMR-based metabolic profiles for blood serum [23,26,30,31,32,33]. Despite the definition of standardized protocols, a strict execution of these protocols within single- or multi-center clinical studies can be challenging when dealing with continuous fluxes of samples, and analytical approaches to monitor the compliance to best practices or to qualify samples available from biobanks are yet to be implemented at the large-scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many standard operating procedures do not use ice for blood collection. However, for metabolomics applications, sample processing on ice is crucial and documentation of the critical pre-analytical steps in a Standard PREanalytical Code (SPREC) is recommended (Betsou et al 2010 ; Bervoets et al 2015 ). Two known metabolites, ascorbic acid and lactic acid, showed the highest temperature-dependent instability and we have demonstrated that their ratio can be used as quality control marker for plasma sample quality evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that a high number of metabolites are significantly altered as a consequence of prolonged processing times at different temperatures, including signaling metabolites, lipids, carbohydrates, and amino acids. However, the most important changes can be associated with energy‐related metabolites (i.e., increased lactate, decreased glucose, and pyruvate), which could be attributable to the anaerobic metabolism of erythrocytes . Thus, as a general recommendation, blood processing times should be reduced to the minimum (preferably no longer than 2 h) and samples should be kept cool in the meantime.…”
Section: Sample Characteristics and Preanalytical Processingmentioning
confidence: 99%